Depth structure of the Gorishne-Plavninsk structure and general principles of geological and geophysical study of the Krivoy Rog-Kremenchug iron-ore strip - Entin, V. A.; Orlyuk, M. I.; Belous, O. I.; Gintov, O.B.; Malakhov, V.G.; Bakhmutov , V.G.; Kachan, I.A.; Bakarzhieva, M.I.; Makarenko, I.B.; Savchenko , O.S.; Samoilenko , T.M.; Marchenko , A.V.; et al. (Geofizicheskiy Zhurnal, 2022)
The article presents the results of the newest research performed by the State Enterprise «Ukrainian Geological Company» and the Institute of Geophysics of the National Academy of Sciences of Ukraine in 2021 to find out the morphology and elements of occurrence of an redeposit within the limits of the Gorishne-Plavninsk-Lavrikovsk area of the Krivoy Rog-Kremenchug iron-ore strip. In the process of geological and geophysical studies, a large body of new geological and geophysical data was obtained regarding the deep structural and morphological features of the construction of the Gorishne-Plavninsk structure (GPS), associated with the Krivoy-Rog deep fracture zone. Materials of reinterpretation of previously per formed ground-based magnetometric and gravimetric surveys, detailed high-altitude aeromagnetic studies and the study of the density and magnetic properties of the structure rocks, including the anisotropy of magnetic susceptibility using new equipment and techniques, gravimagnetic modeling with the construction of three-dimensional volume model of the structure lead to the conclusion that this structure is a typical drag fold with a pronounced reversal of its southern part by the right-hands hear. Its primary formation occurred as a faulted band of sedimentary-volcanogenic and extrusive formations of subvertical bedding and spreading to a depth of at least 1.5—2 km. A complete morphological and kinematic analogue of the GPS is the previously studied Likhmanovsk structure, located in the southern most part of the Krivoy Rog-Kremenchug strip. Many iron-ore structures of the Middle Bug area are close to it in structure and kinematics, the primary subvertical faulting and doubtful sedimentary genesis were mentioned earlier. All these data require a new approach to the study of iron-ore and some other deposits of the Ukrainian Shield associated with fault tectonics, as well as to the genesis problems and stratigraphy of rocks of the Early Precambrian.